Plug-in to After Effects - Yamazaki, Michele (Routledge, 2013)
Take your After Effects projects to the next level by mastering its third-party plug-ins. Whether it's keying and compositing, adding particles of swirling smoke to a composition, or importing XML files from Final Cut Pro, third-party plug-ins can greatly enhance your After Effects capabilities. From sexy effects and graphics enhancements to workflow automation and file conversion, it's all covered in this lavishly illustrated, full-color book. Coverage of hundreds of essential third-party plug-ins is provided, showing you when, why, and how to use each plug-in. Plug-ins for color, style, effects, distortions, warps, transitions, lens flares, text and graphical elements, and more are all covered in depth.